Transcending from veterinary public health to one Health: a review of the role of veterinary medicine in human health (2017)
From the pre-modern era around 475 CE when ‘horse doctoring’ was the subject of veterinary attention because of economic interest to 1762 when the first veterinary school was established to control the devastating economic effects of Rinderpest (Cattle plague) in cattle; basically, veterinary medicine evolved both as a practice and a profession to attend to specific human disease, financial, economic and nutritional needs. It took 250 years after the establishment of the first veterinary school to finally get Rinderpest eradicated worldwide. Meanwhile, environmental degradation/pollution and current modern economic/trade practices have led to an estimated 61% of emerging human infections over the past fifty years or thereabout being zoonotic diseases of human beings transmitted from animals. During the same period, non-zoonotic animal diseases now have serious economic, mortality, public health, trans-boundary and international trade effects; and pets have become significant human emotive partners. These challenges call for an interdisciplinary and multidisciplinary approach, with Veterinary Medicine being the fulcrum of a One Health initiative „to attain optimal health for animal, humans (and plants) in a common environment’. Nigerian veterinarians have the professional agricultural-environmental--medical-veterinary responsibility to have an active and pioneer ‘paradigm shift’ towards instutionalization of One Health in Nigeria, lest it suffers from ‘paradigm paralysis’- a harmful inaction and/or resistance to the imperative of expedient change.